À quoi servaient les remparts des oppida gaulois ? - Pierre Moret (Pallas, 2017)
Questioning the defensive role of the ramparts of Late La Tène oppida is a prevailing tendency in recent Celtic historiography, as it is assumed by most scholars that their function was predominantly symbolic and ostentatious. Lines of reasoning refuting the military functionality of these fortifications, especially the murus gallicus type, are discussed in this paper. Contrary to current interpretations, it appears that the building techniques, morphology and circuit outlines of these structures are perfectly congruent with a well-reasoned plan of defence, adapted to the warfare and siege tactics in use at that time in the Celtic world. From this perspective, their design is in no way less efficient than that of Hellenistic stone-masonry city walls. In the urbanization process that affects the La Tène culture from the third century BC, fortification appears late, a century after the first large proto-urban trading settlements. It is therefore not a fundamental attribute of Celtic urbanism per se and should rather be interpreted as a response to the global threats instigated by the historical conjuncture of 125-100 BC.